Organizational Interest, Nuclear Weapons Scientists, and Nonproliferation. - Weiner, Sharon K. (Political Science Quarterly)
The writer discusses the Nuclear Cities Initiative and Initiatives for Proliferation Prevention, two U.S. programs designed to fight proliferation by providing former Soviet nuclear weapons workers with income. She attributes the programs' blend of successes and failures to organizational interest. She presents three insights offered by the programs into the effect of organizational interest on policy.